Bacteremia and Mortality among Patients with Nontunneled and Tunneled Catheters for Hemodialysis - Carla Santos De Lima; Flora Braga Vaz; Rodrigo Peixoto Campos (International Journal of Nephrology)
Introduction. Central venous catheters for hemodialysis (HD) can be nontunneled catheters (NTC) or tunneled catheters (TC). Bacteremia and dysfunction are complications that can impact morbidity and mortality. We decided to compare the rates of bacteremia and dysfunction between NTC and TC and patient survival 90 days after catheter insertion. Methods. Retrospective cohort to evaluate catheters inserted between January 2011 and December 2020 in a tertiary hospital. Catheters in patients with end-stage chronic kidney disease were included. Patients with acute kidney injury, catheters that lasted less than three HD sessions, and patients who died within one week after insertion were excluded. Bacteremia and dysfunction rates, bacteremia-free survival, and dysfunction-free survival were investigated. Multivariable analysis was performed using a Cox proportional hazards regression model for patient survival at 90 days. Results. 670 catheters were analyzed in 287 patients, 422 NTC (63%), and 248 TC (37%). The rates of confirmed bacteremia per 1,000 catheter-days were 1.19 for NTC and 0.20 for TC (p<0.0001). The confirmed or possible bacteremia rates were 2.27 and 0.37 per 1,000 catheter-days for NTC and TC, respectively (p<0.0001). The dysfunction rates were 3.96 and 0.86 for NTC and TC, respectively (p<0.0001). Patient survival at 90 days was higher in the TC group than the NTC group (96.8% vs. 89.1%; p<0.0001). Conclusion. We found lower rates of bacteremia and dysfunction for TC and demonstrated that using NTC affects patient mortality.